2001
DOI: 10.1097/00006676-200103000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Cholangiopancreatography in Assessing the Cause of Acute Pancreatitis in Children

Abstract: Magnetic resonance cholangiopancreatography (MRCP) is a new noninvasive method of obtaining images of the pancreaticobiliary tract. Recent advances in MR technology and image quality have made it easy to diagnose structural abnormalities of the pancreaticobiliary tract (SAPBT) in children. To examine the usefulness of MRCP in assessing the cause of acute pancreatitis in children, we performed MRCP in 16 patients with acute pancreatitis. The study population was divided into two groups according to the cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…In our review of the literature, we found that 16 of the 18 false negatives and three of the six false positives involved evaluation of the pancreatobiliary junction. MRCP correctly identified anomalous union of the pancreatobiliary junction in 53% to 85% of children with choledochal cysts [18,23], 67% in idiopathic chronic pancreatitis [20], and 69% to 72% in children with known or suspected pancreatobiliary malformation [17,25•]. The reasons for incorrect diagnosis of pancreas divisum and anomalous union of the pancreatobiliary junction include an unclear relationship between the dorsal pancreatic duct and common bile duct, a long inferior branch of the dorsal pancreatic duct crossing a short or fine ventral pancreatic duct, and sphincter of Oddi spasm resulting in an artifactual short common channel length [25•].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our review of the literature, we found that 16 of the 18 false negatives and three of the six false positives involved evaluation of the pancreatobiliary junction. MRCP correctly identified anomalous union of the pancreatobiliary junction in 53% to 85% of children with choledochal cysts [18,23], 67% in idiopathic chronic pancreatitis [20], and 69% to 72% in children with known or suspected pancreatobiliary malformation [17,25•]. The reasons for incorrect diagnosis of pancreas divisum and anomalous union of the pancreatobiliary junction include an unclear relationship between the dorsal pancreatic duct and common bile duct, a long inferior branch of the dorsal pancreatic duct crossing a short or fine ventral pancreatic duct, and sphincter of Oddi spasm resulting in an artifactual short common channel length [25•].…”
Section: Discussionmentioning
confidence: 91%
“…Shimizu et al [18] reported on 16 consecutive children (ages 2.5-15.6 years) evaluated for acute pancreatitis. All children were also studied by ultrasonography.…”
Section: Review Of Studies Comparing Mrcp To Gold Standard Evaluationmentioning
confidence: 99%
“…However, ERCP requires cannulation of the pancreatic duct and the CBD, which carries the risk of several complications including pancreatitis, infection, bleeding, and bile leak [27]. A prospective study by Shimizu et al [28] on the use of MRCP in assessing the causes of acute pancreatitis in children found that it is a useful, noninvasive method in identifying the structural abnormalities of the pancreaticobiliary tree when compared to ERCP. Prasad et al [29] also found that MRCP is a viable noninvasive alternative to ERCP in the assessment of pediatric pancreaticobiliary disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective Hirohashi et al [47] 5 4 0 0 1 HASTE Sugiyama et al [22] 7 5 0 0 2 HASTE Chan et al [44] 6 0 4 0 2 2D TSE Irie et al [56] 16 10 1 0 5 HASTE Matos et al [57] 8 6 2 0 0 SSTSE Miyazaki et al [43] 6 2 3 0 1 HASTE Frampas et al [54] 5 1 4 0 0 HASTE Shimuzu et al [59] 7 6 0 0 1 HASTE Tang et al [77] 10 6 2 0 2 HASTE Kim et al [60] 20 12 3 0 5 SSFSE Park et al [55] 72 34 28 3 7 HASTE Suzuki et al [61] 32 16 2 0 14 HASTE Fitoz et al [62] 5 1 4 0 0 SSFSE Saito et al [64] overall diagnostic accuracy of 56%-100%. In contrast, ERCP has been reported with sensitivity and specificity > 90% for diagnosing APBJ [11] .…”
Section: Detected Not Detectedmentioning
confidence: 99%